2019
DOI: 10.1016/j.acap.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Improving Response Rates and Representation of Hard-to-Reach Groups in Family Experience Surveys

Abstract: The response rate for day of discharge tablet survey administration was >4-fold higher than with single-wave mail-only administration, with greater participation of hard-to-reach groups. These findings suggest tablet administration before discharge shows great promise for real-time feedback and QI and may transform the field of inpatient survey administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…This may be mainly due to our face-to-face mode for data collection, which usually gains higher response rates than mail or telephone approaches. In addition, we believe that the electronic questionnaire and online survey system helped improve the participation of hard-to-reach groups in our trial, as demonstrated by the similar tablet administration in Japan and the US (18)(19)(20).…”
Section: Discussionmentioning
confidence: 88%
“…This may be mainly due to our face-to-face mode for data collection, which usually gains higher response rates than mail or telephone approaches. In addition, we believe that the electronic questionnaire and online survey system helped improve the participation of hard-to-reach groups in our trial, as demonstrated by the similar tablet administration in Japan and the US (18)(19)(20).…”
Section: Discussionmentioning
confidence: 88%
“…In addition, a recent study showed that over 80% of children completing the CLEFT-Q scales, representing 9 of the 12 PROMs in the Set, liked answering the questions, and felt it made them understand their condition and feelings better (Klassen et al, 2020). The fact that the children get something in return (insight in their own well-being, more individualized care) could be a reason for obtaining relatively high response rates in contrast to the reported email survey response rates of 20% to 40% among adults in literature (Rodriguez et al, 2006;Fowler et al, 2019;Toomey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the response rate (35%) was not high. Although it is much higher than that in the U.S. national survey (17.1%) [6], it was lower than those of previously reported surveys using a QR code or special tablet devices (63% and 71%, respectively) [11,27]. Of note, in these previous studies, eligible parents were approached on the day of discharge before they left the hospital, despite the recommendation of the Agency for Healthcare Research and Quality to initiate the survey between 48 h and 6 weeks after discharge.…”
Section: Discussionmentioning
confidence: 63%